PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Sianturi, Sitra; Silalahi, Donalson (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
The purpose of this study was to determine and explain the effect of institutional ownership and managerial ownership on financial performance in LQ-45 companies listed on the Indonesian Stock Exchange for the 2018-2021 period, both simultaneously and partially. To achieve this goal, research was carried out on the Indonesia Stock Exchange using the purposive sampling method for 18 companies for the 2018-2021 period with 72 observations. The analysis technique used is a multiple linear regression model with descriptive statistical tests, classical assumption tests, and hypothesis testing. The results of this study indicate that institutional ownership has a significant and significant effect on financial performance, while managerial ownership has a positive and significant effect on financial performance. Simultaneously institutional ownership and managerial ownership have a positive and significant effect on financial performance with a value (R2) of 20%